2012
DOI: 10.1002/cbf.2854
|View full text |Cite
|
Sign up to set email alerts
|

Effect of progesterone on the expression of GABAA receptor subunits in the prefrontal cortex of rats: implications of sex differences and brain hemisphere

Abstract: Progesterone is a neuroactive hormone with non-genomic effects on GABA(A) receptors (GABA(A)R). Changes in the expression of GABA(A)R subunits are related to depressive-like behaviors in rats. Moreover, sex differences and depressive behaviors have been associated with prefrontal brain asymmetry in rodents and humans. Thus, our objective was to investigate the effect of progesterone on the GABA(A)R α1 and γ2 subunits mRNA expression in the right and left prefrontal cortex of diestrus female and male rats expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
(101 reference statements)
1
18
0
Order By: Relevance
“…However, these authors did not find changes in mRNA expression of the ␣4 subunit in the hippocampus of treated male rats (Nin et al 2008). Another study by our group showed that low doses of progesterone presented an antidepressant-like effect in diestrus female rats, which was associated with increased mRNA expression of the ␣1 subunit in the right prefrontal cortex of female rats (Andrade et al 2012), evidencing a functional asymmetry of the GABA system related to sex and mood disorders. We believe that our data are relevant because most of the currently available studies have not investigated brain asymmetries related to the effect of neurosteroids and their implications in the control of behaviour.…”
Section: Figmentioning
confidence: 87%
See 2 more Smart Citations
“…However, these authors did not find changes in mRNA expression of the ␣4 subunit in the hippocampus of treated male rats (Nin et al 2008). Another study by our group showed that low doses of progesterone presented an antidepressant-like effect in diestrus female rats, which was associated with increased mRNA expression of the ␣1 subunit in the right prefrontal cortex of female rats (Andrade et al 2012), evidencing a functional asymmetry of the GABA system related to sex and mood disorders. We believe that our data are relevant because most of the currently available studies have not investigated brain asymmetries related to the effect of neurosteroids and their implications in the control of behaviour.…”
Section: Figmentioning
confidence: 87%
“…The protein levels were measured following the method of Bradford (1976). Since there is functional asymmetry, and the expression of several genes and proteins are hemispheric-specific in the brain (Andrade et al 2012), we analysed the right and left OBs separately. After protein measurement, sodium dodecyl sulphate -polyacrylamide gel electrophoresis (SDS-PAGE) on 10% (w/v) acrylamide gels was carried out using a mini-protean system (Bio-Rad, Hercules, California, USA) with broad range molecular weight standards (FullRange Rainbow Molecular Weight Markers; GE Healthcare).…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Progesterone can cross the blood-brain barrier, due to its lipophilic structure and acts on receptors located in the central nervous system [4]. Estrogen and progesterone have their respective hormone receptors, whereas allopregnanolone acts via the GABA-A receptor [5].…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone acts as a potent positive modulator of the GABA-A receptor because of its conversion into its metabolite, allopregnanolone. In vitro and in vivo studies have shown that progesterone and allopregnanolone levels are related to GABA-A receptor changes in different regions of the brain [3,4]. However, less is known with regard to the effects of progesterone on the serotonergic system.…”
Section: Introductionmentioning
confidence: 95%